A comparative study of lexical word search in an audioconferencing and a videoconferencing condition. Issue 4 (4th May 2019) - Cohen, Cathy; Wigham, Ciara R.
Abstract: This study on online L2 interactions compares lexical word search between an audioconferencing and a videoconferencing condition. Nine upper-intermediate learners of English describe a previously unseen photograph in either the videoconferencing or the audioconferencing condition. A semantic feature analysis is adopted to compare their interactions. To evaluate the contribution of visual and verbal modes, a quantitative analysis examines the distribution of the referential properties of one target lexical item: tunnel earring . It suggests that pushed output produced in the videoconferencing condition is lexically richer. Then, in view of these results, focusing on two learners, one from the audioconferencing condition and one from the videoconferencing condition, a fine-grained multimodal analysis of the qualitative features of gestures and speech complements the quantitative results. It demonstrates how the videoconferencing condition allows the learner to embody salient physical referential properties of the lexical item, before transferring the referential information to the verbal mode, to produce a semantically rich description. The study will interest researchers working on multimodality and L2 teachers deciding between videoconferencing and audioconferencing as pedagogical options.